Myh6-driven Cre recombinase activates the DNA damage response and the cell cycle in the myocardium in the absence of loxP sites - Xinrui Wang; Amelia Lauth; Tina C. Wan; John W. Lough; John A. Auchampach (The Company of Biologists, 2020)
Regeneration of muscle in the damaged myocardium is a major objective of cardiovascular research, for which purpose many investigators utilize mice containing transgenes encoding Cre recombinase to recombine loxP-flanked target genes. An unfortunate side effect of the Cre-loxP model is the propensity of Cre recombinase to inflict off-target DNA damage, which has been documented in various eukaryotic cell types including cardiomyocytes (CMs). In the heart, reported effects of Cre recombinase include contractile dysfunction, fibrosis, cellular infiltration and induction of the DNA damage response (DDR). During experiments on adult mice containing a widely used Myh6-merCremer transgene, the protein product of which is activated by tamoxifen, we observed large, transient, off-target effects of merCremer, some of which have not previously been reported. On Day 3 after the first of three daily tamoxifen injections, immunofluorescent microscopy of heart sections revealed that the presence of merCremer protein in myonuclei was nearly uniform, thereafter diminishing to near extinction by Day 6; during this time, cardiac function was depressed as determined by echocardiography. On Day 5, peaks of apoptosis and expression of DDR-regulatory genes were observed, highlighted by >25-fold increased expression of Brca1. Concomitantly, the expression of genes encoding cyclin-A2, cyclin-B2 and cyclin-dependent kinase 1, which regulate the G2/S cell-cycle transition, were dramatically increased (>50- to 100-fold). Importantly, immunofluorescent staining revealed that this was accompanied by peaks in Ki67, 5'-bromodeoxyuridine and phosphohistone H3 labeling in non-CMs, as well as CMs. We further document that tamoxifen-induced activation of merCremer exacerbates cardiac dysfunction following myocardial infarction. These findings, when considered in the context of previous reports, indicate that the presence of merCremer in the nucleus induces DNA damage and unscheduled cell-cycle activation. Although these effects are transient, the inclusion of appropriate controls, coupled with an awareness of the defects caused by Cre recombinase, are required to avoid misinterpreting results when using Cre-loxP models for cardiac regeneration studies. This article has an associated First Person interview with the first author of the paper.